2009
DOI: 10.1177/1087057109336751
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inhibition: Deriving KI and kinact Directly from Time-Dependent IC50 Values

Abstract: The potential of enzyme inhibition of a drug is frequently quantified in terms of IC50 values. While this is a suitable quantity for reversible inhibitors, concerns arise when dealing with irreversible, or mechanism-based inhibitors (MBI). IC50 values of MBI are time-dependent, causing serious problems when aiming at ranking different compounds with respect to their inhibitory potential. As a consequence, most studies and ranking schemes related to MBI rely on the inhibition constant (K I ) and the rate of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(165 citation statements)
references
References 40 publications
(74 reference statements)
9
156
0
Order By: Relevance
“…Covalent inhibitors display time-dependent changes in IC 50 values, making it difficult to derive enzyme kinetic parameters (21). Thus, we adapted a liquid chromatography (LC)-MS-based GPX4 assay (2) to measure GPX4 inhibition by (1S, 3R)-RSL3 in a concentration series at a specific time point to determine an effective IC 50 for (1S, 3R)-RSL3.…”
Section: Resultsmentioning
confidence: 99%
“…Covalent inhibitors display time-dependent changes in IC 50 values, making it difficult to derive enzyme kinetic parameters (21). Thus, we adapted a liquid chromatography (LC)-MS-based GPX4 assay (2) to measure GPX4 inhibition by (1S, 3R)-RSL3 in a concentration series at a specific time point to determine an effective IC 50 for (1S, 3R)-RSL3.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to estimate k inact and K I from shifted IC 50 values [based on a modified Cheng and Prusoff (1973) equation] was also validated by Krippendorff et al (2009) both theoretically (in silico) and experimentally using a nondilution approach in which the rate of formation of fluorescent metabolites (one for CYP1A2 and one for CYP3A4) was measured in situ at 2-min intervals (the "progress curve" method). Obach et al (2007) reported a strong empirical correlation between shifted IC 50 values and k inact /K I (as would be expected from the equations above).…”
Section: Discussionmentioning
confidence: 99%
“…The published method of time-dependent inhibition data analysis using an IC 50 -shift experimental setup (Maurer et al, 2000;Berry and Zhao, 2008;Krippendorff et al, 2009) was modified to allow the simultaneous nonlinear regression of the IC 50 curves. It was assumed that substrate metabolism follows Michaelis-Menten kinetics with the rapid equilibrium approximation, the inhibitor is competing with a substrate for the enzyme active site, and the enzyme-inhibitor complex can produce an inactive enzyme (Scheme 3).…”
Section: Time-dependent Inhibition Of Mdz 19-hydroxylation By Emcmentioning
confidence: 99%